Computational research on a combined undulating-motion pattern considering undulations of both the ribbon fin and fish body. (1st July 2019) - Zhao, Zhijie; Dou, Lei
Abstract: In this work, the combined undulating-motion pattern (CUMP) of the undulatory ribbon-fin propulsion is numerically investigated, inspired by the swimming of the large-mouthed catfish ( Silurus soldatovi meridionalis Chen). The swimming of a juvenile large-mouthed catfish is observed and recorded to study the undulation of its elongated anal fin, commonly known as the "ribbon fin". Compared with the knifefish, which undulates the ribbon fin to swim while maintaining a relatively rigid fish body, the large-mouthed catfish performs a CUMP propulsion, which comprises the undulation of the fish body and the active undulation of the ribbon fin. Accordingly, a fin–body fish model is used to study the effect of the CUMP propulsion on the swimming performance. Simulation results show that the phase-angle difference between the undulations of the fish body and the ribbon fin has a significant impact on the thrust and heave forces. More specifically, an in-phase CUMP propulsion, which is commonly found in the swimming of actual large-mouthed catfish, can dramatically improve the thrust. In addition, the effects of the angular amplitude of ribbon fin and the swimming frequency are considered as well. Finally, the reasons for the thrust augmentation in the in-phase CUMP propulsion are detailed and analyzed. Highlights: A novel combined undulating-motion pattern of the undulatory ribbon-fin propulsion is numerically studied. The swimming of a real juvenile large mouthed catfish is recorded and analyzed. A new combined fin–body fish model is proposed to study the combined undulating motion pattern. It is inferred that the fish can get a greater thrust by means of the in-phase combined undulating motion pattern. This paper may provide some new insights to the development of novel biomimetic autonomous underwater vehicles.